Champ 7 Alsace - Tirol. - Bartl, Klaus; Bouteillet, Maïa; Duconseille, François; Froeliger, Eric; Gander, Mario; Gelot, David; Guthmann, F.; Holzinger, Andréa; Hörmann, Magdalena; Jerome, Jean; Pümpel, Norbert; Rychlik, Otmar; et al. (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 1996)
Bartl, Klaus ; Duconseille, François ; Froeliger, Eric ; Gelot, David ; Holzinger, Andréa ; Kogler, Peter ; Kuntzel, Jean-Louis ; Poirot, Pascal ; Pümpel, Norbert ; Stöber, Klaus ; Trawöger, Ernst ; Trenkwalder, Elmar
biog. per kunstenaar
Champ 7 : Alsace - Tirol, CRAC (Centre Rhenan d'Art Contemporain) Alsace, Altkirch, 24 nov. - 29 dec. 1996, Ausstellungsraum Büchsenhausen, Innsbruck, märz 1997
Duits & Frans
boek
Keywords: Alsace; Tirol